Students' Voice Note WhatsApp Group in Speaking Classroom - Zahrotul Cameliya; Moh. Hafidz; Mariyatul Kiptiyah (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2023)
This study aims to make the speaking skills of class X students of SMA Al-Ghozali be better by using voice note WhatsApp group as a learning medium. This research is a qualitative research that aims to find and prove that the use of this media can improve students' speaking skills. The research method used is case studies which is a research process in which researchers get systematic, factual and accurate over vier information about facts and phenomena that happen. Researchers and teachers also play a role in this research process to find out the teaching and learning process using this media and also the weaknesses in the speaking learning process. researchers used 3 instruments to collect data, namely observation, interview and documentation. The researcher made 2 times observation meeting because in the first observation meeting the student's speaking had not been successful for the purpose of this study. English teacher and 5 students became the object of this interview. The second observation meeting showed that the students' speaking skills improved after watching a narrative video, and after students made a voice recording related the video narrative. It was also found that watching the narrative video then recording a voice messages through WhatsApp group was more likely to help them improve their English. Students continue to improve their speaking skills in finding more and more English words by using the voice note WhatsApp group as the media. The indicators of successful implementation are: (1) students perform a voice note WhatsApp group in speaking classroom has a good influence on students and (2) students perceptions of voice note WhatsApp group in peaking classroom also has a great influence on students when they perform their speaking using voice note WhatsApp. In addition, this finding is also supported by the results of student speaking after using voice note WhatsApp group as media in speaking classroom.